Perceived captology strategies in mobile applications: do they differ? - Abdullah, N.A.; Abdul Hamid, Nor Aziati; C., C. Siew; Shamsuddin, Alina; Wahab, Eta (Medwell Publisers, 2018)
Studies on various captology applications have indicated the importance of its integration to ensure mobile application=s success. However, statistics have shown that 53% of mobile applications users had problems with mobile applications and discontinue their use. This raises a question whether incorporating captology strategies has varying effectiveness. Moreover, the studies on captology strategies of mobile application have not been sufficiently researched on as majority of existing studies have been focusing on single application only. Therefore, this study aimed to examine whether there are significant differences of captology principles (reduction, tunneling, tailoring, suggestion, self-monitoring, surveillance and conditioning) between two popular mobile applications which are WhatsApp and Telegram. Using a cross sectional online survey, 364 users of both applications had participated. Descriptive finding indicates that WhatsApp had higher mean values for all captology principles compared to Telegram. T-test result shows significant differences of reduction, tunneling, tailoring, suggestion, self-monitoring, surveillance and conditioning between WhatsApp and Telegram. The higher means obtained by WhatsApp indicated that users of WhatsApp perceive captology principles as being incorporated more effectively in WhatApp compared to Telegram. This implies that any incorporation of captology principles requires in-depth understanding about the dynamic of each principles and how it could improve mobile application=s users acceptance, attitudes and behavior.